Semantics - Saeed, John I. (Wiley, 2016)
Semantics, 4th Edition, presents an engaging and accessible introduction to the study of meaning in language for students new to the field of semantics. Covers all of the basic concepts and methods of the field of semantics, as well as some of the most important ontemporary lines of research Features a series of new exercises, along with their solutions, that are arranged by level of difficulty Addresses componential theory, formal semantics, and cognitive semantics, the three main current theoretical approaches to semantics Includes revisions and updates that reflect the most recent theoretical developments